Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique